The right to be forgotten: a gap between Europe and United States - Moreno Bobadilla, Ángela (2019)
The right to be forgotten has become a matter of capital importance, as a consequence of the impact that the Internet is having on the privacy of citizens. In this context, this article analyzes the different forms of protection of this emerging right in codified systems and common law systems, in order to account for the different realities that are being created in both continents, where the aim is to balance the right to information with the right to be forgotten in an era where digital memory does not forget or forgive.